Bunga rampai sastera Parsi - Muhammad Bukhari Lubis, 1953- (Kuala Lumpur : Dewan Bahasa dan Pustaka, 1990)
Criticism on Persian literature from a Malay writer's viewpoint.
Koleksi Sumbangan : Abdul Ghafar Ibrahim (AGI)
Koleksi Sumbangan Dr Mohd Nasrin.
Includes bibliography and index.
Keywords: Persian literature -- History and criticism